DIFFERENTIATION OF FOCAL NODULAR HYPERPLASIA FROM HEPATOCELLULAR CARCINOMA IN THE NONCIRRHOTIC LIVER WITH A CT-BASED RADIOMICS NOMOGRAM - Turgunov B.Sh; Turakulov U.N; Zhao Zhenhua; Ergashaliev A.G (Scholar Express Journals, 2023)
The main purpose of our study was to develop and validate a radiomics for differentiating focal nodular hyperplasia (FNH) from hepatocellular carcinoma (HCC) in the non-cirrhotic liver before the surgery
Keywords: Focal nodular hyperplasia; Hepatocellular carcinoma; Computer tomography; X-ray